Engaging students with profound and multiple disabilities using humanoid robots - Standen, Penny; Brown, David; Roscoe, Jess; Hedgecock, Joseph; Stewart, David; Galvez Trigo, Maria Jose; Elgajiji, Elmunir (Springer Verlag, 2014)
Engagement is the single best predictor of successful learning for children with intellectual disabilities yet achieving engagement with pupils who have profound or multiple disabilities (PMD) presents a challenge to educators. Robots have been used to engage children with autism but are they effective with pupils whose disabilities limit their ability to control other technology? Learning objectives were identified for eleven pupils with PMD and a humanoid robot was programmed to enable teachers to use it to help pupils achieve these objectives. These changes were evaluated with a series of eleven case studies where teacher-pupil dyads were observed during four planned video recorded sessions. Engagement was rated in a classroom setting and during the last session with the robot. Video recordings were analysed for duration of engagement and teacher assistance and number of goals achieved. Rated engagement was significantly higher with the robot than in the classroom. Observations of engagement, assistance and goal achievement remained at the same level throughout the sessions suggesting no reduction in the novelty factor.